Educational process in Mozambique and parental involvement - Hoguane, Isabel; Pinto, Anselmo Orlando (Advances in Social Sciences Research Journal, 2022)
This article reflects on parental involvement in the school life of children in Mozambique. With this theme, it is intended to understand the level of parental participation in their children’s school life. Methodologically, the study is of a qualitative nature, based on the review of the existing literature on the subject. In addition to the introduction and conclusion, this study is divided into six points, namely: 1) the pedagogical problem - which speaks of education as a fundamental requirement of the human person; 2) parental involvement - conceptual perspective; 3) forms of parental involvement - which can occur at school and at home directly and indirectly; 4) obstacles to parental involvement - the level of education, social class, time, the relationship between school and family, the economic level, the type of family, are some of the obstacles mentioned; 5) impact of parental involvement on learning - parental involvement influences children’s success on three levels: cognitive, emotional and behavioral; and 6) Parental participation in school life in Mozambique - governments from various countries promote an active and democratic participation of society in the management of schools, based on the principle that the school is a heritage of the community. The results of this study indicate that the contribution of parents to their children’s learning at home is still insignificant. Therefore, it is suggested that actions be promoted for greater and better involvement of parents in student learning; the implementation, for example, of parental involvement programs in order to provide parents with the necessary knowledge and strategies for this process.